2019
DOI: 10.30831/akukeg.449484
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğretmenlerinin Görüşlerine Göre Okul Müdürlerinin Sergilediği Teknolojik Liderlik Davranış Düzeyi

Abstract: This research aims to examine the level of technological leadership behaviors of the secondary school principals in the use of technology by teachers according to secondary school teachers' views on the basis of some variables. The quantitative method was used. The study group consisted of 442 teachers from secondary schools in Mamak district of Ankara. The data was collected through "School Principals Technological Leadership Behavior Scale (SPTLB-S)" developed by Durnalı (2018). SPTLB-S consists of eighteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
0
7
0
4
Order By: Relevance
“…Results showed that there is a steady increase in the number of published articles on technology leadership throughout the years. This might be due to the increasing importance given to the critical role of technology leadership in the last years for effective educational environments and practices (Webster, 2017;Durnali, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that there is a steady increase in the number of published articles on technology leadership throughout the years. This might be due to the increasing importance given to the critical role of technology leadership in the last years for effective educational environments and practices (Webster, 2017;Durnali, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Diğer yandan Sezer ve Deryakulu'nun (2012) ilköğretim okul yöneticilerinin teknoloji liderliği rollerine ilişkin yeterliklerini ele aldıkları araştırmalarında, okul yöneticilerinin "gelişim ve değerlendirme", "destek", "planlama ve denetim" ve "etik ve güvenlik" rollerini yerine getirme düzeylerinin yüksek olduğu sonucuna ulaşmışlardır. Ayrıca teknoloji liderliği alanında son yıllarda yapılan çalışmaların, daha çok okul yöneticilerinin teknoloji liderliği öz-yeterliklerine (Çalık, Çoban ve Özdemir, 2019; Gün ve Çoban, 2019) ve ortaokullarda okul müdürlerinin teknoloji liderliği düzeylerine (Durnalı, 2019) odaklanan çoğunlukla nicel yaklaşımla gerçekleştirilmiş araştırılmalar olduğu görülmektedir. Ancak okul yöneticilerinin teknoloji liderliği ile ilgili deneyimlerin detaylı olarak belirlenmesi ve yorumlanmasına yönelik nitel çalışmalara rastlanmamıştır.…”
Section: Teknoloji Lideri Olarak Okul Yöneticileriunclassified
“…It is to use information and communication in the administration of human and material resources and the subordinate and upper systems outside the school (parents, non-governmental organizations, associations, and so on) mainly for realizing the objectives of education and training at the highest level. That is to say, technological leadership is the leadership in the subject of ensuring the benefits of technology at the highest level of effectiveness in creating and sustaining an effective education and training system (Durnalı, 2018;2019). Technological leadership covers a wide area from the lighting system of traditional classrooms or technology classes to the necessary security measures during the use of technology (Micheal, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The first thesis (Tanzer, 2004) among these studies was conducted in 2004. With the implementation of the Ministry of National Education ICT projects such as E-School and the widespread use of the Internet in the last decade, it can be claimed that the number of these studies has widely increased (Çalık, Çoban, & Özdemir, 2019;Çoban, 2021;Durnalı, 2019;Turan, 2020;Turan & Gökbulut, 2022). Specifically, Sincar (2009)'s study on the technology leadership roles of primary school administrators (the example of Gaziantep province) is said to be a turning point for technological leadership studies in Turkey because eight studies focusing on technological leadership have used the instrument developed by Sincar (2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation